Changing views of Cajal's neuron - Azmitia, Efrain C. (Progress in brain research, 2002)
Cajal is the Father of Neuroscience and his personal view of the Neuron has dominated the field for over 100 years. No single person has been able to challenge his global perspective of the neuron gained by Cajal's work in neuroanatomy, development, physiology, evolution and medicine. However, over 30 neuroscientists from around the world have accepted the challenge of writing a review article on "Changing Views of Cajal's Neuron". Many of these experts admitted they could only add to Cajal's theory and they carefully provided their new findings based on modern methods of microscopy, molecular biology or neurobiology. Other experts recognized specific areas where Cajal's ideas of neurons needed to be altered and refined. Key knowledge necessary to understand plasticity or development is now available and permits a changed view. A few of the authors directly challenged some of the most widely accepted and cherished theories of Cajal: the neuron as an isolated unit, function of dendrites, the direction of electrical conductivity and the importance of plasticity in the adult brain. In total, the collection of articles provides a fascinating perspective to the enormous force of Cajal's genius in the 21st Century view of the neuron.